2023
DOI: 10.3390/s23042064
|View full text |Cite
|
Sign up to set email alerts
|

How Accurately Can Wearable Sensors Assess Low Back Disorder Risks during Material Handling? Exploring the Fundamental Capabilities and Limitations of Different Sensor Signals

Abstract: Low back disorders (LBDs) are a leading occupational health issue. Wearable sensors, such as inertial measurement units (IMUs) and/or pressure insoles, could automate and enhance the ergonomic assessment of LBD risks during material handling. However, much remains unknown about which sensor signals to use and how accurately sensors can estimate injury risk. The objective of this study was to address two open questions: (1) How accurately can we estimate LBD risk when combining trunk motion and under-the-foot f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
(78 reference statements)
2
1
0
Order By: Relevance
“…The result of adding relevant types of input sensors to improve the prediction accuracy was in line with prior research [ 43 , 44 ]. For instance, Nurse et al (2023) showed how the combination of pressure insole data with trunk motion increased low back disorder risk estimates from a range of r = 0.20–0.56 to r = 0.93–0.98 [ 43 ].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The result of adding relevant types of input sensors to improve the prediction accuracy was in line with prior research [ 43 , 44 ]. For instance, Nurse et al (2023) showed how the combination of pressure insole data with trunk motion increased low back disorder risk estimates from a range of r = 0.20–0.56 to r = 0.93–0.98 [ 43 ].…”
Section: Discussionsupporting
confidence: 81%
“…The result of adding relevant types of input sensors to improve the prediction accuracy was in line with prior research [ 43 , 44 ]. For instance, Nurse et al (2023) showed how the combination of pressure insole data with trunk motion increased low back disorder risk estimates from a range of r = 0.20–0.56 to r = 0.93–0.98 [ 43 ]. Substituting trunk IMU with thigh or pelvis IMU did not significantly reduce the prediction accuracy; however, removing more relevant sensors, such as force estimates from pressure insoles, significantly reduced low-back-loading estimation accuracy during MMH [ 45 ].…”
Section: Discussionsupporting
confidence: 81%
“…Table 1 shows that most papers in the literature that deal with spinal detection use an inertial measurement unit (IMU) that contains an accelerometer, gyroscope, and magnetometer, yielding all three axis planes. Since IMU sensors can detect spinal disorders, they can be applied to different wearable devices [ 13 , 14 , 15 , 16 , 17 , 18 , 20 , 21 , 22 , 23 , 24 ]. Specifically, some papers dealt with musculoskeletal disorders that are related to UCS such as identifying hunched and slouched back [ 14 ], tracking and monitoring the sitting posture [ 15 ], and embedding IMU sensors in clothing to continuously monitor back posture [ 17 , 19 , 20 ].…”
Section: Related Workmentioning
confidence: 99%